Genetic analysis of grain dimensions and weight and their association with grain yield in rainfed rice (Oryza sativa) - CHAUHAN, J S; CHAUHAN, V S (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during rainy season of 1991 to stud the inheritance of grain size, shape and weight and their interrelationships with grain yield in rainfed rice (Oryza sativa L), Grain length, breadth and shape were found quantitatively inherited and their expression was influenced by modifiers in5 intervarietal crosses, viz 'RR 51-1' x 'Kalinga 3','BG 367-4' X 'RR 149·177', 'BO 367-4' X 'RR 203-2', Annada' x 'Kalinga 3' and' Annada' X 'Prasanna'. The frequency distribution for grain weight in the F2generation of 'BG 367-4' x 'RR 149-177' and 'Annada' X 'Kalinga 3' indicated the segregation of genes of major effect, whereas in the rest of the 3 crosses the expression of grain weight was under polygenic control. High heritability (broad sense) along with high to mooerate expected genetic advance for grain weight, grain length, breadth and shape indicated that selection in the segregating generation might be very useful in the improvement of these characters. There was no consistent trend of interrelationship among grain size, shape, weight and yield.